Improved booth encoding for reduced area multiplier - Hussin, R.; Ali Yeon, Md Shakaff; Idris, N.; Ismail, R.C.; Kamarudin, A. (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org